Fourier analysis of multi-legged periodic gaits - Rodrigues, Carlos M. B. (2019)
This paper analyses periodic gaits of multi-legged locomotion systems. The joint signals are studied in the Fourier domian, namely from the point of view of its reproducibility through low-pass actuators. The influence of several parameters is also considered and their critical values are investigated.